Жена моего мужа: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2001)
Экземпляры: ф. 4 (20130625) / Инвентарный номер: 99833 / Цена: 100.00 / Авт.знак: Д 67 / ББК: 84(2Рос=Рус)6